Structure of a gene encoding a cytosolic acetyl-CoA carboxylase of hexaploid wheat. - Podkowinski, J (1996)
An entire gene encoding wheat (var. Hard Red Winter Tam 107) acetyl-CoA carboxylase [ACCase; acetyl-CoA:carbon-dioxide ligase (ADP-forming), EC 6.4.1.2] has been cloned and sequenced. Comparison of the 12-kb genomic sequence with the 7.4-kb cDNA sequence reported previously revealed 29 introns. Within the coding region, the exon sequence is 98% identical to the known wheat cDNA sequence. A second ACCase gene was identified by sequencing fragments of genomic clones that include the first two exons and the first intron. Additional transcripts were detected by 5' and 3' RACE analysis (rapid amplification of cDNA ends). One set of transcripts had a 5' end sequence identical to the cDNA found previously and another set was identical to the gene reported here. The 3' RACE clones fall into four distinguishable sequence sets, bringing the number of ACCase sequences to six. None of these cDNA or genomic clones encodes a chloroplast targeting signal. Identification of six different sequences suggests that either the cytosolic ACCase genes are duplicated in the three chromosome sets in hexaploid wheat or that each of the six alleles of the cytosolic ACCase gene has a readily distinguishable DNA sequence.